Deploying Resilience ?: Family Farming and Food Systems in the Context of Covid-19 - Rengifo Briceño, Gabriela (2021)
The Provincial Municipality of Huancayo participates in the Milan Pact, an agreement to promote sustainable food systems that promotes agro-ecological production. Junín is the first region, at the national level, in which a pilot of public purchases of fresh products is carried out for the National School Food Program Qali Warma. During the most critical months of the pandemic, the price of potatoes in the Maltería de Huancayo market fell to 30 cents per kilo and the price on the farm to 10 cents. Although natural persons represent the bulk of the number of agricultural units, most of the agricultural area is managed by peasant communities. Thus, 88.48% of the agricultural area in Concepción is managed by peasant communities, 86.52% in Huancayo, 81.36% in Jauja, 75.65% in Tayacaja and 62.99% in Chupaca. The percentage of agricultural units in the five provinces is less than 3 hectares, being Tayacaja the one that presents 83% of lands smaller than 3 hectares and Huancayo with 91%.